KLAIM ROYALTI LAGU DAN/ATAU MUSIK PENCIPTA DAN HAK TERKAIT DI PLATFORM YOUTUBE SEBAGAI BENTUK PEMENUHAN HAK KEADILAN - Dewi, Rien Uthami; Triningsih, Anna (Lex Jurnalica, 2025)
AbstrakRoyalty claims for the use of copyright of songs and/or musics of Creators and Related Rights by users on digital platforms are very important as a form of fulfillment of the right to justice for Creators and Related Rights who have economic rights besides moral rights. Protection of songs and/or musics have been regulated by law in Indonesia, in regulation of Copyright Number 28 of 2014, and regulation related to royalties in Government Regulation Number 56 of 2021 on Management of Copyright Royalties for Songs and/or Music. However, in the context of platforms that are providers of song services in digital form (digital service providers), or those based on user generated content (UGC) such as YouTube, the existing regulations are inadequate so that more specific regulatory updates and adjustments are needed because the tendency of existing digital platforms to have different provisions from regulations in Indonesia. It can be said that there is a legal vacuum regarding the accountability of digital service providers who allow the broadcast of songs or masters unlawfully. Especially if the provider as the provider of the song and/or music service has entity the holding company outside Indonesia. There is a rejection or rebuttal that will be submitted if a dispute/problem occurs regarding music content. For example, a digital service provider will state that it is not obligated to compensate for content uploaded by user generated content, but is limited to deleting content that is disputed and proven to be done unlawfully. Regarding royalty claims, YouTube will respond that YouTube does the same thing as it does with other countries, namely by entering into legal relations with legal subjects in the form of private legal entities, based on confidentiality agreements. The losses experienced by Creators and Related Rights Owners as an artist in the creative arts economy are not small, even though if royalties are managed with good governance and users who utilize song and/or music are subject realize to their obligations to pay royalties, it will have a potential impact on the income of the country where the song was created. The government is expected to be able to look ahead and carry out what must be done as the legal adage says